The determinants of high school closures: lessons from longitudinal data throughout Illinois - Sherrilyn M. Billger; Frank D. Beck (Institute for the Study of Labor (IZA), 2009)
Facing substantial financial pressure, many districts close schools in order to preserve solvency and improve student outcomes. Using a new longitudinal data set on all non-Cook County Illinois schools, we examine the determinants of high school closure decisions from 1991 through 2005. Our dataset combines information from a wide variety of sources, including the Illinois State Board of Education, the Census Bureau, the Illinois Department of Revenue, and the Bureau of Labor Statistics. Prior studies in this area typically use cross-sectional data, short panels, or case-studies. Schools that close have lower enrollments, are located in more rural areas, and have higher per-pupil expenditures. Enrollments and fiscal resources are indeed the most important determinants of school closures. Neither math and reading test scores nor the sociodemographics of the students have a significant impact on high school closure decisions.
Keywords: I22; I21; J24; 330; Economics of education; education finance; human capital; secondary education; Allgemeinbildende Schule; Liquidation; Schulfinanzierung; Bildungsverhalten; Bildungsökonomik; Schätzung; Illinois